Pelanggaran Etika Pariwara Indonesia pada Akun Instagram @gatotkoco.id - Hanifah, Nurul; Faturrochman, Azis; Praweni, Dea Senja; Arifianto, Budi Dwi (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to examine violations of the Indonesian Advertising Ethics (EPI) in the advertising content of Gatotkoco coffee products uploaded on the Instagram account @gatotkocoid. The research highlights the need to understand the application of ethics in the rapidly growing digital advertising landscape. Using a qualitative descriptive approach with documentation and literature review methods, the findings reveal violations of Article 1.26 of the EPI, which prohibits the exploitation of sexuality in advertisements. These violations are evident in visuals and narratives that are irrelevant to the product but highlight suggestive sexual elements. This study underscores the importance of understanding and applying advertising ethics to prevent negative impacts such as the normalization of gender exploitation and negative public perception of the brand. The findings contribute to the literature on advertising ethics and offer recommendations for industry practitioners to create more socially responsible advertisements.